1997
DOI: 10.1017/s0140525x97001581
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of cognitive development: A constructivist manifesto

Abstract: How do minds emerge from developing brains? According to “neural constructivism,” the representational features of cortex are built from the dynamic interaction between neural growth mechanisms and environmentally derived neural activity. Contrary to popular selectionist models that emphasize regressive mechanisms, the neurobiological evidence suggests that this growth is a progressive increase in the representational properties of cortex. The interaction between the environment and neural growth result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
305
1
19

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 690 publications
(340 citation statements)
references
References 396 publications
(164 reference statements)
15
305
1
19
Order By: Relevance
“…In connection with this, it is interesting to note a parallel "neuroconstructivist" movement focused on internal structures and mechanisms that attempts to chart a middle way between the extremes of nativism (too much prespecified structure) and empiricism (too little structure) to explain the development of higher-order capacities through the child's interaction with a progressively structured, even necessarily social environment (Elman et al 1996;Karmiloff-Smith 1998;Quartz & Sejnowsky 1997). Given the similarity of constructivist ambitions, there may be fruitful connections to exploit between these two programs.…”
Section: Orlando@fculptmentioning
confidence: 99%
“…In connection with this, it is interesting to note a parallel "neuroconstructivist" movement focused on internal structures and mechanisms that attempts to chart a middle way between the extremes of nativism (too much prespecified structure) and empiricism (too little structure) to explain the development of higher-order capacities through the child's interaction with a progressively structured, even necessarily social environment (Elman et al 1996;Karmiloff-Smith 1998;Quartz & Sejnowsky 1997). Given the similarity of constructivist ambitions, there may be fruitful connections to exploit between these two programs.…”
Section: Orlando@fculptmentioning
confidence: 99%
“…For example, Purves et al (1996) and Quartz and Sejnowski (1997) Garson 2012 for further discussion). Those critics tend to think of neural selection as a "two-step" process in which, at birth there is a large number of synapses that get progressively whittled down in early development (e.g., Purves et al 1996, 461;Quartz and Sejnowski 1997, 539).…”
Section: A Generalized Se Theory Of Functionmentioning
confidence: 99%
“…For example, a recent functional MRI study reported that visual representations of faces are "pruned back" during early childhood (14). Such purported explanations fail to account for the fact that the brain does not shrink during postnatal development but grows in size, and that the loss of synaptic connections is only one phenomenon in the context of several other mechanisms of selective synaptic growth and elaboration (15,16). In the present context, the lack of N170 tuning in congenital cataract participants would typically evoke a "pruning" explanation: a failure to eliminate incorrect synapses.…”
Section: Mechanisms: Tuning or Pruning?mentioning
confidence: 99%